RECENT ADVANCES IN ELUCIDATING THE BIOLOGICAL AND CHEMICAL PROPERTIES OF STRYCHNOS POTATORUM LINN. F. - A REVIEW - SRIKANTH KAGITHOJU; VIKRAM GODISHALA; MADHUSUDHAN KAIRAMKONDA; HIMABINDU KURRA; RAMA SWAMY NANNA (International Journal of Pharma and Bio Sciences, 2012)
Strychnos potatorum Linn.F. is a medicinally important endangered forest tree species which belongs to Loganiaceae and is also known as nirmali and clearing nut tree. In traditional medicinal systems like Ayurveda, Siddha and Greek, the plant parts are used for treating eye and urinary tract infections; gonorrhoea and kidney troubles, leucorrhoea, tuberculosis, diabetes, venereal diseases and acute diarrhea. The plant showed the presence of various important phytochemical constituents which may be responsible for many of the pharmacological activities such as diuretic activity, antidiarrhoeal activity, contraceptive efficacy, hepatoprotectivity, antioxidant activity, antiarthritic activity, antiulcerogenic activity, antinociceptive and antipyretic effects. But the mechanism of action for these properties is not fully understood. The findings presented in this review indicate that this plant should be studied more extensively to confirm these properties and to reveal other potential therapeutic uses.